DAMPAK PANDEMIK COVID-19 TERHADAP PROSES PEMBELAJARAN ONLINE DI SMP NEGERI 1 BARUS UTARA - Muhammad Syahril Harahap; Zulfadly Zulfadly; Elsa Putri Simatupang (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
The background of this research is Covid- 19 pandemic in world. Especially in Indonesia, Minister of Education issued a circular number 3 in 2020 concerning the change of offline learning to online. The approach of the research is descriptive qualitative. The informants are the parents and the students of SMP Negeri 1 Barus Utara. The data analysis used Miles and Huberman. The result of the research showed there are some impacts experienced by parents and students in learning online in Covid-19 pandemic period which included students are forced to be independently and study diligently, students get difficulty in understanding the topic, students are burdened with online learning, students know more about information and technology, students use more handphone, the parents  are able to see the development of the students when they are learning, there are extra work of the parents in accompanying the students when study, and there are extra cost to buy internet quota. It’s concluded learning online gives positive and negative impacts on parents and students of SMP Negeri 1 Barus Utara.